An Earth Hazards Camp to Encourage Minority Participation in the Geosciences. Issue 1 (14th March 2017) - Sherman-Morris, Kathleen; Clary, Renee M.; McNeal, Karen S.; Diaz-Ramirez, Jairo; Brown, Michael E.
ABSTRACT: Summer camps have proven to be effective tools to engage students in the geosciences. Findings from this study highlight perceptions and experiences of middle school students from predominantly African American school districts in Mississippi who attended a 3-d residence camp focused on increasing interest in the geosciences through an earth hazards theme. The 2013 summer camp was structured to emphasize three subject areas: geology, hydrology, and meteorology. Nine middle school students (seven males and two females) attended the camp developed and held at Mississippi State University. Students' pre- and postcamp understanding about geoscience processes and interest in and knowledge about geoscience careers were measured to evaluate the camp's success. Overall interest in geosciences increased after completing the program. Among the three subject areas emphasized in this camp, students gained more knowledge about geology than about the other two areas (hydrology and meteorology). Results indicate that hands-on and experiential learning methods, especially those held indoors or with optimal conditions outdoors, were most successful at stimulating interest.